IMPLEMENTATION OF THE INHERITANCE OF INDONESIAN CITIZENS OF CHINESE DESCENT IN PALU CITY, CENTRAL SULAWESI PROVINCE - Dikky Patenjenu; Maisa; Heru Wardoyo (Program Pascasarjana Universitas Muhammadiyah Palu, 2023)
The implementation of the inheritance of the Chinese-descended community in Palu City prioritizes Chinese customary law in the distribution of their inheritance because the distribution of inheritance according to the Civil Code is contrary to Chinese customary law. The share of inheritance for sons and daughters is the same, contrary to the teachings of Confucius. The settlement of inheritance disputes is pursued in two ways, namely through non-litigation (mediation) and litigation (court). In reality, the settlement of inheritance disputes prioritizes non-litigation or family deliberations rather than using litigation or courts because the use of litigation is a disgrace for Chinese citizens so that the application of inheritance law for the Chinese community and ways of resolving inheritance disputes can inspire an equal and humane law enforcement model in the future.